Adaptation strategy for sustainable food sovereignty based on vulnerability and climate risk assessment : a case study of Sulawesi Island. Issue 1 (April 2020) - Estiningtyas, Woro; Perdinan,; Rahman, Adi; Suciantini,
Abstract: Food is an important element to human life. Food availability is a main factor to support sustainable agricultural activities. Concrete efforts are urged to support the Indonesian government targets to become the world food basket by 2045. Extreme climate events leading to climate related hazards such as floods and drought that significantly impact negatively planting area, harvesting, and production must be addressed so the risks can be minimized. Vulnerability and risk assessment of climate impacts on food farming system are completed to provide information on the vulnerability level in each district/city to determine contributing factors that influence the vulnerability level. Data on climate, land, and water resources as well as socio economic were selected to represent the indicators for vulnerability assessment. The indicators were grouped into Exposure and Sensitivity Index-Indeks Keterpaparan dan Sensitivitas (IKS) and Adaptation Capacity Index-Indeks Kapasitas Adaptasi (IKA). The vulnerability and risk assessments to floods for Sulawesi Island explain that there are about 8% of districts/cities grouped into the level of very high category and about 17% of the districts/cities grouped into the level of high category. As for the vulnerability and risk to drought, the assessments show that about 1% of districts/cities are included into the level of extreme high category, about 8% grouped into the level of very high category, and about 17% classified into the level of high category. The contributing factors to the IKA are the length of the road based on surface conditions and the ratio of the number of farmer groups per paddy area. The IKS dominant determinants that must be addressed are climate. The level of vulnerability and determinant factors are useful to assist in preparing strategies and recommended programs of adaptation actions compounded with priority districts/cities whose levels of vulnerability are categorized into high, very high, and extreme high.